Meltwater characteristics as indicators of the hydrology of Alpine glaciers - Collins, David Nigel (1979)
Hydrological, hydrochemical and sedimentological observations were undertaken in the catchments of Feevispa (Feegletscher), Findelenbach(Findelengletscher) and Gornera (Gornergletscher), Swiss Alps, in an attempt to use meltwater characteristics as indicators of the nature and functioning of glacial hydrological systems.